18Ffluorocholine PET vs. 99mTcsestamibi scintigraphy for detection and localization of hyperfunctioning parathyroid glands in patients with primary hyperparathyroidism - Rep, Sebastijan (Radiology and oncology (Ljubljana), 2024)
Minimally invasive parathyroidectomy is the treatment of choice in patients with primary hyperparathyroidism (PHP), but it needs a reliable preoperative localization method to detect hyperfunctioning parathyroid tissue. Higher sensitivity and lower radiation exposure was demonstrated for 18Ffluorocholine PET/CT (FCh-PET/CT) in comparison to 99mTcsestamibi (MIBI) scintigraphy. However, data of its efficiency in resource use and patient outcomes is lacking. The aim of our study was to determine the resource efficiency and patient outcomes of FCh-PET/CT in comparison to conventional MIBI scintigraphy. Patients and methods A group of 234 patients who underwent surgery after MIBI scintigraphy was compared to a group of 163 patients who underwent surgery after FCh-PET/CT. The whole working process from the implementation of imaging to the completion of surgical treatment was analyzed. The economic burden was expressed in the time needed for the required procedures. Results The time needed to perform imaging was reduced by 83% after FCh-PET/CT in comparison to MIBI scintigraphy. The time needed to perform surgery was reduced by 41% when intraoperative parathyroid hormone monitoring was not used. There was no significant difference in the time of surgery between FCh-PET/CT and MIBI scintigraphy. Conclusions FCh-PET/CT reduces the time of imaging, the time of surgery and potentially reduces the number of reoperations for persistent disease.
Keywords: hiperparatiroidizem; kirurgija; paratiroidektomija; scintigrafija; stroškovna učinkovitost